Impact of geographic diversity on citation of collaborative research - Naik, Cian; Sugimoto, Cassidy R.; Larivière, Vincent; Leng, Chenlei; Guo, Weisi (Elsevier, 2023)
Diversity in human capital is widely seen as critical to creating holistic and high-quality research, especially in areas that engage with diverse cultures, environments, and challenges. Quantification of diverse academic collaborations and their effect on research quality is lacking, especially at international scale and across different domains. Here, we present the first effort to measure the impact of geographic diversity in coauthorships on the citation of their papers across different academic domains. Our results unequivocally show that geographic coauthor diversity improves paper citation, but very long distance collaborations have variable impact. We also discover “well-trodden” collaboration circles that yield much less impact than similar travel distances. These relationships are observed to exist across different subject areas, but with varying strengths. These findings can help academics identify new opportunities from a diversity perspective, as well as inform funders on areas that require additional mobility support.
Keywords: geography; diversity; citation; collaborative research; air travel